2014
DOI: 10.1186/bf03352257
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimates of relationships between geomagnetic activity and equatorial spread-F as determined by TID occurrence levels

Abstract: Using a world-wide set of stations for 15 years, quantitative estimates of changes to equatorial spread-F (ESF) occurrence rates obtained from ionogram scalings, have been determined for a range of geomagnetic activity (GA) levels, as well as for four different levels of solar activity. Average occurrence rates were used as a reference. The percentage changes vary significantly depending on these subdivisions. For example for very high GA the inverse association is recorded by a change of −33% for R z ≥ 150, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The relationship does not depend on equatorial electric fields or the vertical drifts produced by them. Furthermore, this inverse effect has been reported for low latitudes [see Bowman , 1998, Figure 1] and for midlatitudes [see Bowman and Mortimer , 2000, Figure 5]. In contrast, the literature contains many papers that examine, at specific times, relationships between active GA, particularly, geomagnetic storms, and SSIs (ESF s ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The relationship does not depend on equatorial electric fields or the vertical drifts produced by them. Furthermore, this inverse effect has been reported for low latitudes [see Bowman , 1998, Figure 1] and for midlatitudes [see Bowman and Mortimer , 2000, Figure 5]. In contrast, the literature contains many papers that examine, at specific times, relationships between active GA, particularly, geomagnetic storms, and SSIs (ESF s ).…”
Section: Discussionmentioning
confidence: 95%
“…Subdivisions of data were made for this series, which involved PM and AM intervals, R z max and R z min periods, equatorial stations across the world and stations at other latitudes. The results for all these analyses were obtained at high levels of statistical significance [ Bowman , 1987, 1995a, 1998; Bowman and Mortimer , 2000]. Using airglow recordings for two decades at an equatorial station, near an anomaly crest location, Sobral et al [2002] have reported decreased SFO for increased GA involving K p index levels associated with delays >4 h before sunset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found for the extensive superposed-epoch analyses of this kind that the final displacements are distributed normally (see e.g. Bowman and Mortimer, 2000). Consequently on Fig.…”
Section: The Detection Of Long Delaysmentioning
confidence: 99%
“…They found 33 % decline in SF occurrence rate when the geomagnetic activity was high and the international sunspot number (Rz) was higher than 150 (Bowman & Mortimer, 2000). It is thus worth checking what effect geomagnetic activity has on SF occurrence according to our model.…”
Section: Sf Occurrence Relation To Geomagnetic Activitymentioning
confidence: 75%